The Effect of Using e-Books with the STEM-PjBL Approach on Students' Learning Motivation and Creative Thinking Ability - Mela Mahardika Ilafi; Suyanta Suyanta; Insih Wilujeng; Sabar Nurohman (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to determine the effect of e-book teaching materials on Temperature and Heat Science materials packaged with the STEM-PjBL approach in increasing students' learning motivation and creative thinking abilities. This research uses a quasi-experimental quantitative research method with a one group pretest-posttest design. The subjects in this research were 32 students in class VII C of SMP Negeri 5 Depok. The results of the research that has been carried out show the high learning motivation of students. For each indicator the conformity point is above 50%, so in this case it can be stated that students' opinions are more interested in using STEM-PjBL based science e-books. Meanwhile, students' creative thinking abilities show N-Gain values ​​in each aspect, namely fluency of 0.45, flexibility of 0.38, novelty of 0.61, and usefulness of 0.62. The average N-Gain for creative thinking ability is 0.52 in the "Medium" category. In this way, STEM-PjBL based science e-books can create learning motivation and creative thinking abilities in students